The Thai version of the PSS-10: An Investigation of its psychometric properties - Nahathai Wongpakaran (2018)
Background: Among the stress instruments that measure the degree to which life events are perceived as stressful, the Perceived Stress Scale (PSS) is widely used. The goal of this study was to examine the psychometric properties of a Thai version of the PSS-10 (T-PSS-10) with a clinical and non-clinical sample. Internal consistency, test-retest reliability, concurrent validity, and the factorial structure of the scale were tested.Methods: A total sample of 479 adult participants was recruited for the study: 368 medical students and 111 patients from two hospitals in Northern Thailand. The T-PSS-10 was used along with the Thai version of State Trait Anxiety Inventory (STAI), the Thai Version of the Rosenberg Self-Esteem Scale (RSES), and the Thai Depression Inventory (TDI).Results: Exploratory Factor Analysis (EFA) yielded 2 factors with eigenvalues of 5.05 and 1.60, accounting for 66 percent of variance. Factor 1 consisted of 6 items representing "stress"; whereas Factor 2 consisted of 4 items representing "control". The item loadings ranged from 0.547 to 0.881. Investigation of the fit indices associated with Maximum Likelihood (ML) estimation revealed that the two-factor solution was adequate [χ2 = 35.035 (df = 26, N = 368, p < 0.111)]; Goodness-of-Fit Index (GFI) = 0.981; Root Mean Square Residual (RMR) = 0.022; Standardized Root Mean square Residual (SRMR) = 0.037, Comparative Fit Index (CFI) = 0.989; Normed Fit Index (NFI) = 0.96, Non-Normed Fit Index (NNFI) = 0.981, Root Mean Square Error of Approximation (RMSEA) = 0.031. It was found that the T-PSS-10 had a significant positive correlation with the STAI (r = 0.60, p < 0.0001), and the TDI (r = 0.55, p < 0.0001); and was significantly negatively correlated with the RSES (r = -0.46, p < 0.0001, N = 368). The overall Cronbach's alpha was 0.85. The ICC was 0.82 (95% CI, 0.72 and 0.88) at 4 week-retest reliability.Conclusions: The Thai version of the PSS-10 demonstrated excellent goodness-of-fit for the two factor solution model, as well as good reliability and validity for estimating the level of stress perception with a Thai population. Limitations of the study are discussed. © 2010 Wongpakaran et al; licensee BioMed Central Ltd.